Крепление высокотемпературных скважин в коррозионно-активных средах - Кравцов В. М. Владимир Михайлович; Кузнецов Ю. С. Юрий Степанович; Мавлютов М. Р. Мидхат Акрамович; Агзамов Ф. А. (Москва, Недра, 1987)
Авт. указаны на обороте тит. л.